Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T14:16:47+01:00
A)(a+2ab+b)-(a-2ab)+b=a+2ab+b-a+2ab+b=4ab+2b

b)(ay-3a*5y-5 2/3)-(4ay-3 2/3)=ay-15ay-5 2/3-4ay+3 2/3=-18ay-2

c)-(b² -2b+5)+b+3b-b²=-b²+2b-5+b+3b-b²=-2b²+6b-5

d)5a*2-2a*2 -(a-a^2)-(12a-4a^2)=10a-4a-a+2a-12a+8a=3a

LICZE NA MAXA
WŁASNIE NIEDAWNO SKOŃCZYŁAM TEN DZIAŁ;)
2010-03-09T14:25:25+01:00
A)(a+2ab+b)-(a-2ab)+b=
=a+2ab+b-a+2ab+b=
=2b+4ab

b)(ay-3a*5y-5 2/3)-(4ay-3 2/3)=
=ay-15ay-5 2/3-4ay+3 2/3=
=-18ay-2

c)-(b² -2b+5)+b+3b-b²=
=-b²+2b-5+b+3b-b²=
=-2b²+6b-5

d)5a²-2a² -(a-a²)-(12a-4a²)=
=3a²-a+a²-12a+4a²=
=8a²-13a